Implementasi Peraturan Daerah Nomor 6 Tahun 2008 Terhadap Usaha Industri Di Kabupaten Labuhanbatu - Sumitro Sarkum; Maya Jannah; Nimrot Siahaan (IKA BINA EN PABOLO : PENGABDIAN KEPADA MASYARAKAT, 2021)
The problem raised in this paper is how to regulate the granting of permits in the laws and regulations relating to the granting of industrial business licenses in Labuhanbatu Regency, how to procedure for granting industrial business licenses in Labuhanbatu Law No. 6/2008 by Labuhanbatu Regency government, the method used in This writing is using normative legal research conducted with research data dissemination. The granting of industrial business licenses by local governments is one of the supporting factors for regional development, because by granting business licenses, levies on regions are increasing and the cost of fees can be a fund for the regions in carrying out regional development efforts. Legislation related to Industrial Business licenses are as follows: Law No. 3 of 2014 concerning Industry, Government Regulation Number 13 of 1995 jo Government Regulation Number 107 of 2015 concerning Industrial Business Permits, Minister of Industry Regulation Number 41/M-IND/Per/6/2008 jo regulation of the Minister of Industry Number 81/M-IND/Per/10/2014 concerning the provisions and procedures for granting Industrial business licenses, expansion permits and registration marks, regulation of the minister of industry number 05/M-IND/Per/2/2014 concerning procedures, Granting of Industrial Estate Business Permits and Industrial Estate Extension Permits. The procedure for obtaining an Industrial Business Permit is by: The applicant takes care of the recommendation letter from the local lurah and sub-district head and completes other required documents; Applicant fills out the Industrial Business Permit application form available at the Labuhanbatu Regency Licensing Services Office; The applicant submits the completed application form and other administrative requirements; Furthermore, officers will check or inspect the company location. If passed the inspection and other administrative documents have been declared complete, the Industrial Business License will be issued and the applicant can take it at the Labuhanbatu Licensing Service Office.